2011
DOI: 10.5539/ass.v7n12p79
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Moderating Effects of MNCs’ Country of Origin in the Relationship between Degree of Inter-Firm Technology Transfer and Local Firms’ Performance

Abstract: The main objective of this paper is to empirically examine the moderating effect of MNCs' country of origin (Western vs. Asian MNCs) in the relationships between degree of inter-firm technology transfer and two dimensions of local firms' performance: corporate and human resource performances. Using the moderated multiple regression (MMR) analysis, the theoretical models and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Firms achieve many benefits after JV. Wahab et al, (2011) stated that IJVs provide opportunities of transferring capabilities, technologies, learning, productivity and the economic growth of the host country. They studied and compared various forms of strategic alliance like distribution and supply agreements, R&D partnerships or technical and management contract.…”
Section: Jvmentioning
confidence: 99%
See 1 more Smart Citation
“…Firms achieve many benefits after JV. Wahab et al, (2011) stated that IJVs provide opportunities of transferring capabilities, technologies, learning, productivity and the economic growth of the host country. They studied and compared various forms of strategic alliance like distribution and supply agreements, R&D partnerships or technical and management contract.…”
Section: Jvmentioning
confidence: 99%
“…They further stated that honesty, trust and commitment are good strategies to make the JV process more successful. Wahab et al, (2011) suggested that future studies should explore the area. Researchers should investigate the effect of other aspects like culture, collaborative know-how, prior JV experience and learning capacity during IJV process and performance.…”
Section: Jvmentioning
confidence: 99%
“…As a result of the systemic literature search, the review included the results of research on technology acquisition performance by Lin et al (2004), Lin et al (2009), Li (2010), Jabar and Soosay (2010), Sazali et al (2011), Grimpe and Hussinger (2013), Nguyen and Aoyama (2014), and Iyengar et al (2015). The review is structured based on the Siegel and Wright (2015) research on the technology transfer centres in the higher education institutions, technology licencing and start-up creation.…”
Section: Systematic Review Of Inbound Technology Transfer Performance Literaturementioning
confidence: 99%
“…(Appendix 2 continued) Source Measurement Sazali et al (2011) The variable is characterised by-1) tacit knowledge in terms of new product/service development, managerial systems and practice, process designs and new marketing expertise, and 2) explicit knowledge in terms of manufacturing/service techniques/skills, promotion techniques/skills, distribution know-how and purchasing know-how.…”
Section: Lin Et Al (2004)mentioning
confidence: 99%
See 1 more Smart Citation